PENGARUH HARGA, KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN (PADA TOKO BAJU YONGKI) - Fauziah A. Zuhra; Satria Mirsya Affandy Nasution (CERED Indonesia Institute, 2026)
The purpose of this study is to know and analyze the influence of price, service quality on purchase decisions through Purchase Decisions at (Yongki Clothing Store). The method used in this study is using the associative approach method. The population in this study is Yongki store customers, the number of samples used in this study is 100 respondents. The data collection technique used in this study is using questionnaires. The data analysis technique in this study uses descriptive statistical analysis and data analysis with partial least square (PLS). The data processing in this study uses the Smart PLS software program. Based on the results of the study, it shows that Price has a positive effect on Customer Satisfaction, Service Quality has a positive effect on Customer Satisfaction, Purchase Decision has a positive effect on Customer Satisfaction, Price does not have a positive effect on Purchase Decision, Purchase Decision mediates the relationship between price does not have a positive effect on Customer Satisfaction, Purchase Decision mediates the relationship between Service Quality has a positive effect on Customer Satisfaction. Customer Satisfaction